Impact of the Guru Penggerak Programme on Improving Leadership Competence in Numeracy Learning - Imron Imron; Amir Mahmud; Achmad Samsudin (Universitas Tadulako, 2023)
Education of Guru Penggerak is the Government's innovation to prepare for future leadership transformation. Before becoming a leader, the teacher mobiliser is required to be the main actor in classroom learning and mobilise peers through a community of practice. Thus, they are expected to become leaders in school management and development. Candidate of Guru Penggerak, after undergoing Education and Training for 6 months covering 10 modules, will become student-centred learning leaders. The implementation of quality student-centred learning has not been optimal and equitable from one region to another. The low level of literacy and numeracy in the education report card has led the Government to launch the Merdeka Belajar Programme. The purpose of the research conducted on prospective Guru Penggerak is to determine the impact of Education of Guru Penggerak on improving learning through improving grades during education and increasing competence in self-development and learning leadership, knowing the motivation of prospective Guru Penggerak after completing education and whether literacy and numeracy materials are needed. The research method uses quantitative descriptive research using data collection techniques of interviews, documentation, questionnaires and observations, pre-test-post test scores and questionnaires on prospective Guru Penggerak. The results obtained from this study are an average increase from the pre-test score of 50.80 to the average post-test score of 64.58 or an increase of 13.77. From the questionnaire, the competence of self-development and others increased from 76.82% to 87.35%. For learning leadership competence there was an increase from 73.03% to 85.04%